Influence of Ce, Nd, Sm and Gd oxides on the properties of alkaline-earth borosilicate glass sealant - Nibedita Sasmal; Mrinmoy Garai; Basudeb Karmakar (Journal of Asian Ceramic Societies, 2016)
In this study, the influence of CeO2, Nd2O3, Sm2O3 and Gd2O3 on various properties of the melt-quench route derived SrO–CaO–ZnO–B2O3–SiO2 glass have been investigated. Both the precursor glasses and heat treated glasses are characterized by dilatometry, differential scanning calorimetry (DSC), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transformed infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). The density and coefficient of thermal expansion of the glasses varies in the range 3.557–3.804 g cm−3 and 10.5–11.2 × 10−6 K−1 (50–800 °C) respectively. Decrease in crystallization tendency with increase in cationic field strength of the ions is well supported by the increasing crystallization activation energy of the glasses calculated by Kissinger, Augis–Bennett and Ozawa models. XPS study revealed the presence of both Ce3+ and Ce4+ ions and an increase in characteristic binding energy of the respective rare earth elements from their core level studies. The Knoop hardness of the glasses varies in the range 6.03–6.28 GPa. The glass transition, glass softening and crystallization temperature; density and hardness of the glasses increased with increase in cationic field strength of the incorporated ions. The thermomechanical properties of the Gd2O3 containing glass advocate its applicability as the most promising sealant in solid oxide fuel cell.